Hemodynamic analysis of a novel bioresorbable scaffold in porcine coronary artery model. Issue 6 (26th August 2017) - Tenekecioglu, Erhan; Torii, Ryo; Bourantas, Christos V.; Cavalcante, Rafael; Sotomi, Yohei; Zeng, Yaping; Collet, Carlos; Crake, Tom; Abizaid, Alexandre; Onuma, Yoshinobu; Su, Solomon; Santoso, Teguh; et al.
Abstract: Background: The shear stress distribution assessment can provide useful insights for the hemodynamic performance of the implanted stent/scaffold. Our aim was to investigate the effect of a novel bioresorbable scaffold, Mirage on local hemodynamics in animal models. Method: The main epicardial coronary arteries of 7 healthy mini‐pigs were implanted with 11 Mirage Microfiber sirolimus‐eluting Bioresorbable Scaffolds (MMSES). Optical coherence tomography (OCT) was performed post scaffold implantation and the obtained images were fused with angiographic data to reconstruct the coronary artery anatomy. Blood flow simulation was performed and Endothelial Shear Stress(ESS) distribution was estimated for each of the 11 scaffolds. ESS data were extracted in each circumferential 5‐degree subunit of each cross‐section in the scaffolded segment. The generalized linear mixed‐effect analysis was implemented for the comparison of ESS in two scaffold groups; 150‐µm strut thickness MMSES and 125‐µm strut thickness MMSES. Results: ESS was significantly higher in MMSES (150 µm) [0.85(0.49–1.40) Pa], compared to MMSES (125 µm) [0.68(0.35–1.18) Pa]. Both MMSES (150 µm) and MMSES (125 µm) revealed low recirculation zone percentages per luminal surface area [3.17% ± 1.97% in MMSES (150 µm), 2.71% ± 1.32% in MMSES (125 µm)]. Conclusion: Thinner strut Mirage scaffolds induced lower shear stress due to the small size vessels treated as compared to the thick strut version of the Mirage which was implanted in relatively bigger size vessels. Vessel size should be taken into account in planning BRS implantation. Small vessels may not get benefit from BRS implantation even with a streamlined strut profile. This pilot study warrants comparative assessment with commercially available bioresorbable scaffolds.